Nias Dance Encyclopedia as a Source of the Working Process - Tuti Rahayu Sibuea; Wiflihani (Britain International for Academic Research (BIAR) Publisher, 2022)
This study aims to develop an encyclopedia on the concept of traditional dances from Nias ethnic groups in North Sumatra as a source of learning in the process of creating. This research is directed at a reference book product in the form of an encyclopedia. From this research process, the results of the development of a reference book for the local traditional dance of Nias, North Sumatra emerged. This research uses research and development (Research and Development or R&D) methods. The location or place in this study was carried out in the cities of Medan and Nias with data collection techniques obtained through observation, in-depth interviews and documentation. After all the required data have been completed, the next step is to analyze the data using a qualitative paradigm using project based research, which is obtained through data reduction,The average value obtained during the material expert feasibility test was 4.75 with a very good category and no revision. The average value obtained at the time of this media feasibility test was 4.375 with a very good category.The results of the development of this Nias traditional dance encyclopedia book can be used as a reference for students and the community as a source of the creative process for Nias traditional dances.